Enhancing Reading Comprehension Through Mind Mapping: A Classroom Action Research Study with Fifth-Grade Elementary Students - Sarah Azizah; Muhammad Aqil; Zulnuraini Zulnuraini; Ammar Abdullah Joni Guci; Surahman Wilade; Sisriawan Lapasere (Papanda Publisher, 2026)
Reading comprehension remains a persistent challenge in elementary education, with students frequently struggling to organize textual information and identify main ideas. This study investigated the effectiveness of mind mapping strategies in enhancing reading comprehension among fifth-grade students. Employing a classroom action research design based on the Kemmis and McTaggart model, this study involved 33 fifth-grade students at SD Inpres 3 Tondo across two iterative cycles. Data were collected through observation sheets for teacher and student activities, reading comprehension rubrics, and documentation. Analysis combined descriptive statistics for quantitative data and thematic analysis for qualitative observations. Reading comprehension performance improved significantly from 63% (sufficient category) in Cycle I to 79% (good category) in Cycle II, representing a 16-percentage-point increase. Student engagement increased from 65% to 91%, while teacher effectiveness improved from 89% to 95%. An unexpected finding revealed that struggling readers benefited disproportionately from the intervention, showing 24-percentage-point gains compared to 12-percentage-point improvements among higher-performing students. The findings support dual coding theory and schema theory, demonstrating that visual-verbal integration through mind mapping facilitates deeper cognitive processing. Mind mapping proved effective as an accessible, low-cost intervention that transforms comprehension from an invisible individual activity into a visible collaborative process, with implications for literacy instruction in resource-constrained contexts.